2016
DOI: 10.1210/jc.2015-3403
|View full text |Cite
|
Sign up to set email alerts
|

JAG1 Loss-Of-Function Variations as a Novel Predisposing Event in the Pathogenesis of Congenital Thyroid Defects

Abstract: clinical and experimental data indicate that ALGS1 patients have an increased risk of nonautoimmune hypothyroidism, and that variations in JAG1 gene can contribute to the pathogenesis of variable congenital thyroid defects, including CH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 26 publications
3
39
0
3
Order By: Relevance
“…Human heterozygous loss‐of‐function JAG1 mutations are associated with Alagille syndrome type 1 (ALGS1), which is characterized by variable involvement of liver, heart, skeleton, eye and facial defects. Evaluation of thyroid function in 21 cases with Alagille syndrome showed that variations in JAG1 gene can contribute to the pathogenesis of variable congenital thyroid defects, including TD …”
Section: Molecular Defects Associated To Td In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Human heterozygous loss‐of‐function JAG1 mutations are associated with Alagille syndrome type 1 (ALGS1), which is characterized by variable involvement of liver, heart, skeleton, eye and facial defects. Evaluation of thyroid function in 21 cases with Alagille syndrome showed that variations in JAG1 gene can contribute to the pathogenesis of variable congenital thyroid defects, including TD …”
Section: Molecular Defects Associated To Td In Humansmentioning
confidence: 99%
“…Evaluation of thyroid function in 21 cases with Alagille syndrome showed that variations in JAG1 gene can contribute to the pathogenesis of variable congenital thyroid defects, including TD. 59…”
Section: Glis3mentioning
confidence: 99%
“…Congenital thyroid dysfunction may also arise in the context of other complex disorders, such as Alagille syndrome type 1 due to JAG1 mutations (ALGS1) [35] and hepatic or parotid massive hemangiomas, which may produce the thyroid hormone–inactivating enzyme type 3 iodothyronine deiodinase [36, 37]. …”
Section: Mild Hypothyroidism In Neonatesmentioning
confidence: 99%
“…Abnormalities at any step of thyroid development may result in TD associated with hypothyroidism or not (Maiorana et al , ). Previous studies of sporadic and familial TD covering a wide clinical spectrum identified mutations in nine genes: PAX8 , NKX2‐1 , FOXE1 , NKX2‐5 , TSHR, GLIS3, NTN1 , JAG1 and BOREALIN (Dentice et al , ; Senée et al , ; Carré et al , , , ; Sura‐Trueba et al , ; Ramos et al , ; Opitz et al , ; de Filippis et al , ). However, mutations in these genes are found in only 5% of all patients with TD and identification of causative mutations remains a challenging task.…”
Section: Introductionmentioning
confidence: 99%